Energy Efficient Smart Phones for 5G Networks - Radwan, Ayman (Springer, 2015)
This book addresses current technology trends and requirements leading towards the next era in mobile communication handsets; and beyond that the book proposes innovative solutions that could be candidate solutions for 5G phones. It adopts a multidisciplinary and interdisciplinary stance towards handset design, a necessary ingredient if 5th Generation handset and services are to really take-off. Therefore the scope of the book targets a broad range of subjects, including energy efficiency, RF design, cooperation, context-aware systems, roaming, and short-range networking, all of which working in synergy to provide seamless mobility and high speed connectivity within a HetNet environment.